Analysis for Genetic Modifiers of Disease Severity in Patients With Long-QT Syndrome Type 2. (June 2015) - Kolder, Iris C.R.M.; Tanck, Michael W.T.; Postema, Pieter G.; Barc, Julien; Sinner, Moritz F.; Zumhagen, Sven; Husemann, Anja; Stallmeyer, Birgit; Koopmann, Tamara T.; Hofman, Nynke; Pfeufer, Arne; Lichtner, Peter; et al.
Abstract : Background—: Considerable interest exists in the identification of genetic modifiers of disease severity in the long-QT syndrome (LQTS) as their identification may contribute to refinement of risk stratification. Methods and Results—: We searched for single-nucleotide polymorphisms (SNPs) that modulate the corrected QT (QTc)-interval and the occurrence of cardiac events in 639 patients harboring different mutations in KCNH2 . We analyzed 1201 SNPs in and around 18 candidate genes, and in another approach investigated 22 independent SNPs previously identified as modulators of QTc-interval in genome-wide association studies in the general population. In an analysis for quantitative effects on the QTc-interval, 3 independent SNPs at NOS1AP (rs10494366, P =9.5×10 −8 ; rs12143842, P =4.8×10 −7 ; and rs2880058, P =8.6×10 −7 ) were strongly associated with the QTc-interval with marked effects (>12 ms/allele). Analysis of patients versus general population controls uncovered enrichment of QTc-prolonging alleles in patients for 2 SNPs, located respectively at NOS1AP (rs12029454; odds ratio, 1.85; 95% confidence interval, 1.32–2.59; P =3×10 −4 ) and KCNQ1 (rs12576239; odds ratio, 1.84; 95% confidence interval, 1.31–2.60; P =5×10 −4 ). An analysis of the cumulative effect of the 6 NOS1AP SNPs by means of a multilocus genetic risk score (GRS NOS1AP ) uncovered a strong linear relationship between GRS NOS1AP and the QTc-interval ( P =4.2×10 −7 ). Furthermore, patients with a GRS NOS1AP in the lowest quartile had a lower relative risk of cardiac events compared with patients in the other quartiles combined ( P =0.039). Conclusions—: We uncovered unexpectedly large effects of NOS1AP SNPs on the QTc-interval and a trend for effects on risk of cardiac events. For the first time, we linked common genetic variation at KCNQ1 with risk of long-QT syndrome. Abstract : Supplemental Digital Content is available in the text.